Perspektif Filsafat Matematika Dalam Alkitab Di Era Disrupsi - Dian Juli Adisaputra; Aji Suseno (Manna Rafflesia, 2022)
Mathematics is an absolute truth that has a definite value, and mathematics is a science that studies numbers, numbers, formulas, and calculation analyses. While the Bible is the living Word of God as a guide for Christian beliefs. One of the results of the development of mathematical philosophy of thought in the current era of disruption is that humans can experience the Bible in digital form. This writing uses the Literature Study method, and the results of this study show that the perspective of the philosophy of mathematics in the Bible shows the perfection of God in every calculation. It should be understood together that without realizing the results of the proof of every mathematical calculation in this paper is the result of the formulation of God's mathematical philosophy which has been applied to an object of Bible texts related to mathematics.